TINJAUAN HUKUM PERKAWINAN SIRI (TIDAK DICATATKAN) TERHADAP KEDUDUKAN ISTRI DALAM HUKUM ISLAM DAN UNDANG-UNDANG PERKAWINAN - Rafiqi, Rafiqi (Jurnal Ilmiah Penegakan Hukum, 2015)
Marriage constitutes a part sacred life, since has to notice Norma and life method insociety. With justifications motive sort, marriage is done through model sort as wed as runsaway with, wedding contracts until popularmarriage at society, which is wedding siri.Whatever its reason, siri's marriage not good impact for continuity of its family. Effect lawfor marriage what do deed have no gotten married, husband judicial formality ala / wife andchild that be borne can't do civilization's legal action gets bearing with its family. Childrenjust admitted by state as child of extern marries that just have civilization's relationshipwith mother and its mother family.